DAMPAK KEBIJAKAN IZIN PERTAMBANGAN BAGI MASYARAKAT DI KELURAHAN BATUPUTIH BAWAH KECAMATAN RANOWULU KOTA BITUNG - MAKADISI, NOVITA FLORA; PANGKEY, MASJE; TULUSAN, FEMMY (Sam Ratulangi University, 2021)
Mining is an activity carried out by mining entrepreneurs with the aim of obtaining mining goodsand profits from mining products. The reality is that the life of the community around the mine,such as in Batu Putih Bawah Village, Ranowulu District, Bitung City, is still less accepting ofmining, there are still people who do not agree with mining. This research was conducted on April27, 2021. The purpose of this study is to describe the Impact of Permit Mining for the Communityin Batu Putih Bawah Village, Ranowulu District, Bitung City. The research method used isqualitative research methods, as well as data collection techniques carried out in this studythrough interviews, observation and documentation. The conclusion drawn from this study is thatresearchers found differences in perceptions or responses to information from both the miningcompany (company management), the government around the mine, the community who work asmining workers and people who are not mine workers. as follows, (1) the impact The positive thingsthat occur are, increasing community income, increasing job opportunities and job opportunitiesfor local communities, especially for people in Batu Putih Bawah Village, increasing programassistance from mining companies as well as reducing unemployment and increasing spending ongoods. and services. (2) The negative impacts that occur include environmental damage, such asdeforestation, soil erosion, air pollution due to pollution and sedimentation of the remains of wastedumped into the sea which results in a decrease in fisherman catches, a decrease in farmers' yields,an improvement in public health conditions in the area. Lower Batuputih Village.Keywords: Impact, Policy, Licensing, Mining